2022
DOI: 10.4239/wjd.v13.i2.97
|View full text |Cite
|
Sign up to set email alerts
|

Altered spontaneous brain activity patterns in patients with diabetic retinopathy using amplitude of low-frequency fluctuation

Abstract: BACKGROUND Diabetes mellitus is a metabolic disorder characterized by prolonged elevation of blood glucose due to various causes. Currently, the relationship between diabetic retinopathy (DR) and altered connectivity of brain function is unclear. AIM To investigate the relationship between this brain activity and clinical manifestations and behaviors of DR patients by using the amplitude of low-frequency fluctuation (ALFF) technique. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Brain plasticity can be studied with a number of methods, such as electroencephalography (EEG)/evoked potentials (ERPs), structural and functional MRI and transcranial magnetic stimulation (TMS). In addition to functional brain response 47 50 illustrated herein, recent work showed structural changes in the brain after long-duration space flights 4 – 7 resulting from alterations in sleep performance or functional brain networks. Both aspects were estimated by HRV in a healthy astronaut who also took part in repeated space missions 20 , 21 , 28 .…”
Section: Discussionmentioning
confidence: 74%
“…Brain plasticity can be studied with a number of methods, such as electroencephalography (EEG)/evoked potentials (ERPs), structural and functional MRI and transcranial magnetic stimulation (TMS). In addition to functional brain response 47 50 illustrated herein, recent work showed structural changes in the brain after long-duration space flights 4 – 7 resulting from alterations in sleep performance or functional brain networks. Both aspects were estimated by HRV in a healthy astronaut who also took part in repeated space missions 20 , 21 , 28 .…”
Section: Discussionmentioning
confidence: 74%
“…This finding indicates that HDAC7 may play a detrimental role in DR by promoting endothelial dysfunction. Diabetic damage can promote the growth of neovascularization, abnormal growth of neovascularization can cause bleeding, scar, which can lead to retinal detachment [26][27] . A large number of studies have shown that HDACs can promote cell proliferation by regulating the expression and activity of cyclin proteins.…”
Section: Discussionmentioning
confidence: 99%